2015
DOI: 10.1007/s00231-015-1642-z
|View full text |Cite
|
Sign up to set email alerts
|

Inverse conjugate mixed convection in a vertical substrate with protruding heat sources: a combined experimental and numerical study

Abstract: heat inputs, CFD simulations were again run to compare the temperature distribution at the back of the PCB board with measurements. List of symbolsa Absorption coefficient (m −1 ) A Area of heat source (m 2 ) B Distance from the edge of the plate to the nearest chip edge (m) C p Specific heat (J/kg k) D Spacing between the heat sources (m) d Height of the heat source (m) Gr Grashof number, Gr = gβ∆TL 3 υ 2 g Acceleration due to gravity (9.81 m/s 2 ) H Height of the duct/channel (m) h Convective heat transfer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Their study showed that the ANN was able to accurately predict temperature trend of air-flow and plate. Ahamad and Balaji [21] developed an ANN to solve the inverse conjugate heat transfer problem, i. e. the heat source was predicted with trained temperature distribution by ANN. They validated the efficiency and accuracy of the ANN by comparing ANN predictions with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed that the ANN was able to accurately predict temperature trend of air-flow and plate. Ahamad and Balaji [21] developed an ANN to solve the inverse conjugate heat transfer problem, i. e. the heat source was predicted with trained temperature distribution by ANN. They validated the efficiency and accuracy of the ANN by comparing ANN predictions with experimental data.…”
Section: Introductionmentioning
confidence: 99%